2014
DOI: 10.11002/kjfp.2014.21.4.483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mulberry concentrate on lipid oxidation of Yackwa during its storage

Abstract: This study was conducted to evaluate the quality and to inhibit the lipid oxidation of Yackwa with 0, 1, 2, or 3% mulberry concentrate added. We stored Yackwa at 60°C for three weeks. After the three-week storage, the acid value of the Yackwa with mulberry concentrate was lower than that of the control Yackwa. The hydroperoxide value (22.39 meq/kg) of the Yackwa with 3% mulberry concentrate at two weeks of storage was 50% lower than that of the control Yackwa (47.03 meq/kg). Also, after three-week storage, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Since deep-frying is involved in making yakgwa, the most critical factor to determine its quality during preparation and marketing is lipid oxidation. Storage stability of yakgwa was extensively studied in 1990s; effects of frying oil (Min et al, 1985), mulberry or ginger addition to the flour dough (Lee and Park, 1995;Shin et al, 2014), and soaking in sugar syrup or honey (Lee and Park, 1995) on the storage stability of yakgwa were reported. However, most of these studies reported reduced lipid oxidation of yakgwa without relating it with responsible minor compounds derived from ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Since deep-frying is involved in making yakgwa, the most critical factor to determine its quality during preparation and marketing is lipid oxidation. Storage stability of yakgwa was extensively studied in 1990s; effects of frying oil (Min et al, 1985), mulberry or ginger addition to the flour dough (Lee and Park, 1995;Shin et al, 2014), and soaking in sugar syrup or honey (Lee and Park, 1995) on the storage stability of yakgwa were reported. However, most of these studies reported reduced lipid oxidation of yakgwa without relating it with responsible minor compounds derived from ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…오디는 뽕나무(Morous alba L.)과에 속하는 낙엽교목인 뽕나무 열매로 한방에서는 상심(桑椹), 상실(桑實) 또는 흑 심(黑椹) 등으로 지칭되며, 동의보감 탕액편에는 '오디는 성질이 차고 맛이 달며 독이 없고, 당뇨(소갈)을 덜어주며, 오장을 편하게 하고, 오래먹으면 배가 고프지 않게 된다'고 하며, '오디를 오래 먹으면 백발이 검게 변하고, 노화를 방지한다'고 기록되어 있다 (4,5). 또한, 완숙 오디는 당도가 높고 식감이 좋으며, 다량의 glucose와 fructose를 함유하고 (6), oxalic acid, citric acid, malic acid, succinic acid 및 acetic acid와 같은 유기산 (7), polyphenol 및 cyanidin-3-glucoside 와 cyanidin-3-rutinoside 같은 anthocyanin 계통의 색소 등을 다량 함유하고 있어 (8), 식품에 첨가 시 색이 우수할 뿐 아니라, 항산화, 항당뇨, 항고지혈증 등의 다양한 생리활성 효과도 알려지면서 인체에 무해한 천연색소 및 기능성 소재 로 각광받고 있다 (9)(10)(11). 하지만, 오디의 과실은 쉽게 물러 지고, 수분함량이 높아 수확 작업이 어렵고, 쉽게 부패되며 저장성이 떨어져 생과로서의 이용이 불안정하므로 다양한 가공 제품 형태로의 적용이 요구된다 (12).…”
unclassified